PENGARUH SERVICE STANDARD COMMUNICATION DAN KOMITMEN MANAJEMEN TERHADAP KUALITAS LAYANAN DAN KEPUASAN PELANGGAN - Firdaus, Nailufar; Sari Maduratna, Enggal; Sakti, Eklamsia (NHM PRESS, 2023)
Nowadays, competition has occurred in various business fields, both in the manufacturing and service sectors. Organizations must have the right strategy in order to win competition in the industry so that the organization can develop for the long term. These existing challenges also affect the business world related to health services. Over the last thirty years, there has been an increasing need for quality healthcare services to improve lifestyles. Improving the quality of health services is a major concern for patients, and providing better services for patients has become the focus of hospitals (Jandavath and Byram, 2016). The community's increasing need for health services is not being balanced by adequate services from community health centers. Puskesmas is a health service facility that carries out public health efforts and first-level individual health efforts, by prioritizing promotive and preventive efforts, to achieve the highest level of public health in its working area (RI Minister of Health Regulation No. 43, 2019) This research design uses a quantitative research design, with a case study approach. The variables studied are independent variables, including Service Standard Communication and Management Commitment, while the dependent variables are Service Quality and Customer Satisfaction. The research was conducted from November 2023 to February 2024 at the Socah Community Health Center, Bangkalan. The population is 128 patients who have received service at the Socah Community Health Center for an average of 1 month, using simple random sampling with a sample size of 98 people. The data collection tool uses a questionnaire. Data analysis used univariate and bivariate analysis with the Spearman rank statistical test.